Small prosthetic groups in 18F-radiochemistry: useful auxiliaries for the design of 18F-PET tracers - Schirrmacher, Ralf; Wängler, Björn; Wängler, Carmen (Seminars in nuclear medicine, 2017)
Prosthetic group (PG) applications in 18F-radiochemistry play a pivotal role among current 18F-labeling techniques for the development and availability of 18F-labeled imaging probes for PET (Wahl, 2002) (1). The introduction and popularization of PGs in the mid-80s by pioneers in 18F-radiochemistry has profoundly changed the landscape of available tracers for PET and has led to a multitude of new imaging agents based on simple and efficiently synthesized PGs. Because of the chemical nature of anionic 18F− (apart from electrophilic low specific activity 18F-fluorine), radiochemistry before the introduction of PGs was limited to simple nucleophilic substitutions of leaving group containing precursor molecules. These precursors were not always available, and some target compounds were either hard to synthesize or not obtainable at all. Even with the advent of recently introduced “late-stage fluorination” techniques for the 18F-fluorination of deactivated aromatic systems, PGs will continue to play a central role in 18F-radiochemistry because of their robust and almost universal usability. The importance of PGs in radiochemistry is shown by its current significance in tracer development and exemplified by an overview of selected methodologies for PG attachment to PET tracer molecules. Especially, click-chemistry approaches to PG conjugation, while furthering the historical evolution of PGs in PET tracer design, play a most influential role in modern PG utilization. All earlier and recent multifaceted approaches in PG development have significantly enriched the contingent of modern 18F-radiochemistry procedures and will continue to do so.
Gesehen am 11.09.2018
Available online 17 July 2017
Die Zahl 18 ist im Titel jeweils hochgestellt